On CBDC and the need for public debate: Policy and the concept of process - Jamie Morgan (Economic Thought, 2023)
According to the Principle of Techno-Geek Proportionality, for every million times a nerd gets excited about "the latest thing" the world might change once. Central bank digital currency (CBDC) may be that once. There is nothing new about digital money, but there may be many profoundly new things about CBDC. This is especially so for "retail" CBDC - that is, CBDC freely available to the public rather than "wholesale" CBDC, which is restricted to some registered users and central bank systems. At the moment, the vast majority of money in existence takes the form of deposits at Santander, Barclays and the other commercial banks. As the Bank of England makes clear, most of this is originally produced when a bank extends a loan and creates a sum as a deposit which the borrower can then spend. This money flows around our payments system and the money supply, albeit there is more to money supply than just this, grows as cumulative debt grows and shrinks as debt is paid down. In the UK (and equivalents apply in any modern economy that has commercial banks), though we rarely think about it, since the money is denominated in s and the central bank essentially guarantees that it will exchange at par for central bank money, most of what we think of as money is really Santander or Barclays etc. credit units. Retail CBDC could change this state of affairs and the issues are sufficient to require public debate - not only regarding the scope of the technology but also the role and adequacy of central banks. This, in turn, provides an opportunity to discuss the nature of process.
Keywords: 330